Equity gap? - Which equity gap? On the financing structure of Germany's Mittelstand - Christina E. Bannier; Michael H. Grote (Frankfurt School of Finance & Management, 2008)
This paper examines the financing structure of small and medium-sized enterprises (SMEs) in Germany and questions whether an equity gap - or, more generally, a financing gap -exists. Reviewing the literature and available data sources, we find that financing constraints seem to affect, if at all, only a very small subgroup among highly growth-oriented firms. We do not detect any structural problems in average SME's capital structure. Rather, German Mittelstand firms appear to be non-growth oriented and content with their financing decisions. While the relationship-based German banking system helps to minimize the risk of credit rationing, trade credit offers an additional, stable form of liquidity insurance. Highly innovative firms with strong growth potential, on the other hand, do seize the opportunity to tap unconventional means of financing (e.g. mezzanine capital) and appear very successful in doing so.
urn:nbn:de:101:1-20081202209
Keywords: G32; 330; Equity gap; capital structure; financing gap; financing structure; SME